The crisis of collective employment relations systems - Stanojević, Miroslav (Teorija in praksa, 2019)
The present article looks at the situation of collective employment relations in Slovenia, Croatia, Serbia, Hungary and Austria in the period 2013-2015 following the crisis. A review of empirical data shows the countries in our sample differ greatly in the stages of (under)development of collective employment relations and/or dynamics of their destabilisation. The varying levels of both unemployment pressure and trade union power (or lack thereof) explain these differences. The analysis shows the mechanisms destabilising the collective employment relations systems - which underpin such differences - are in essence similar across the sample with characteristic similarities being found in the same sectors in the countries.
Keywords: Delavski sveti; Delovna razmerja; Industrial relations; kadrovska politika; Labor unions; Sindikati; Works council